The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1177/0034355219889409
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Brief Meeting on Employer Attitudes, Knowledge, and Intent to Hire

Abstract: We evaluated the ability of an intervention that consisted of a one-on-one meeting between a vocational rehabilitation (VR) professional and an employer to improve employer attitudes, knowledge, and intent to hire people who are blind or visually impaired. We evaluated the relative effectiveness of two approaches (dual customer vs. educational) and the impact of the VR professionals’ vision status (blind or sighted) on our primary outcome measures and on interest in follow-up. Participants were 59 hiring manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 45 publications
0
2
1
Order By: Relevance
“…It is important to recognize that implicit attitudes may be more difficult to alter than explicit attitudes (Jost et al, 2004). Findings from an associated study of this intervention presented in an earlier article documented a large improvement in explicit attitudes of these same hiring managers (McDonnall & Antonelli, 2019), but the present study documented only a small improvement in implicit attitudes. Implicit associations are often picked up not just by our experiences but also by the culture in which we live, and we have limited cognitive control over these implicit associations, despite new information obtained about the capabilities of people who are blind.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…It is important to recognize that implicit attitudes may be more difficult to alter than explicit attitudes (Jost et al, 2004). Findings from an associated study of this intervention presented in an earlier article documented a large improvement in explicit attitudes of these same hiring managers (McDonnall & Antonelli, 2019), but the present study documented only a small improvement in implicit attitudes. Implicit associations are often picked up not just by our experiences but also by the culture in which we live, and we have limited cognitive control over these implicit associations, despite new information obtained about the capabilities of people who are blind.…”
Section: Discussioncontrasting
confidence: 63%
“…Participants completed the IAT-BVI along with other measures that were collected as part of a larger study involving this intervention; see McDonnall and Antonelli (2019) for details. Participants completed the IAT-BVI online as a pre-test measure within the week before their scheduled meeting with the VR professional.…”
Section: Methodsmentioning
confidence: 99%
“…The 2021 salary survey by the Commission on Rehabilitation Counselor Certification showed 12% of certified rehabilitation counselors worked in for-profit businesses (CRCC, 2021). In spite of this low utilization of VR services, research has shown that intervention by a VR professional can improve employment opportunities for PWD (McDonnall & Antonelli, 2020).…”
Section: Disability Supports and Policies Provided To Employees With ...mentioning
confidence: 99%